2007
DOI: 10.1002/jbm.b.30771
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial flexural modulus of antibiotic‐impregnated orthopedic bone cement

Abstract: Previously reported antibiotic-impregnated cement strengths have been based on uniaxial and fatigue testing methodologies. These methods may not provide an accurate characterization of bone cement's true load-bearing capacity in total joint replacement (TJR). The present study utilized biaxial testing to report on the properties of antibiotic-impregnated cement. Test groups included: PMMA mixed with Vancomycin, Gentamicin, Tobramycin, or no antibiotic (control). In comparison to the control group, PMMA samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…Pilot data confirmed that the silicone spray did not change the impact strength of the test specimens, as reported in other works [7]. The final configuration of each sample resembled a rectangular block measuring 63.5x12.7x12.7 mm.…”
Section: Preparation Of Specimenssupporting
confidence: 84%
See 2 more Smart Citations
“…Pilot data confirmed that the silicone spray did not change the impact strength of the test specimens, as reported in other works [7]. The final configuration of each sample resembled a rectangular block measuring 63.5x12.7x12.7 mm.…”
Section: Preparation Of Specimenssupporting
confidence: 84%
“…Cement testing studies have incorporated different testing methodologies and conditions resulting in a wide range of reported findings. The cement strength studies have been based on uniaxial, biaxial and fatigue testing methodologies using tension, flexural, or compressive testing [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Among the reported properties, the impact strength of bone cement has received very little attention; with the only reports are those by Ungethulum and Hinterberger [21], Ege [22] and Lewis and Mladsi [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors report data from ALBC made with liquid antimicrobial [4,5,9,14]; however, only Seldes [14] and Hseih et al [6] report release data. Seldes [14] did not describe his methods or analysis in sufficient detail to compare his data with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Young's modulus is also decreased more [9]. Antibacterials are generally soluble in water but not in methyl methacrylate (MMA) monomer.…”
Section: Introductionmentioning
confidence: 99%